ANALISIS KINERJA TENAGA PRESENTER LAPANGAN PADA PENERIMAAN MAHASISWA BARU PERIODE JANUARI S/D JUNI 2017 DI POLITEKNIK PGRI BANTEN - Arief Rahman Arief Rahman (NIAGARA Scientific Journal, 2017)
“Analysis Of Performance Field Presenter on New Admisions Period on January Until June 2017” (case study at Politeknik PGRI Banten). The project conducted to know the analysis of performance field presenter wich is used by Politeknik PGRI Banten on new admission. The method of this research paper use descriptive quantitative and data collected method. Questionnaire and to the chosen sampling Politeknik PGRI Banten among employees, to be able to provide a general overview of the performance field presenter located at Politeknik PGRI Banten. Based on the result of the analysis and discussion of problems it can be concluded that in general performance filed presenter at Politeknik PGRI Banten was good. Although there are several criteria that are still under average, but using controlling and coaching well it can be improved. The average score from this research is about 3,7 (scala 5). So the performace field presenter at Politeknik PGRI Banten good enough, the great score included the element of devotion, honesty, loyalty, willingness to work, cooperation and responsibility. While under average score included the indicator of initiative, job performance, improvement and discipline of work.